Awareness Regarding Usage of Interdental Aids and their Role in Oral Hygiene among Medical Undergraduates in District Sheikhupura, Pakistan-A Questionnaire-Based Study - Farhan Riaz, Afifa Ehsan, Naila Umer, Ejaz Hussain Sahu, Ali Raza, Muhammad Behzad Salahuddin (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The contemplations and actions of medical undergraduates concerning their oral well-being mirror their perception of the significance of interdental cleaning aids in the maintenance of oral hygiene. The current study aimed to evaluate understanding and discernment of the practice of interdental aids as well as their role in the maintenance of oral hygiene among medical undergraduates in the district of Sheikhupura, Pakistan. Methods: A questionnaire-based cross-sectional analysis was performed from June 2021 to December 2021 at Amna Inayat Medical College in the district of Sheikhupura, Pakistan on a total of 220 medical undergraduates who were enrolled by convenient sampling method. Data were assembled using a standardized questionnaire that was circulated amongst students of 1st Year MBBS to Final Year MBBS. Associations between awareness regarding interdental cleaning and oral hygiene practice among both genders and all the years of study were assessed through the Pearson Chi-Square test. Results: The study comprised 123 females and 97 males with an average age range of 18 - 25 years. Most of the students i.e. 47.3% knew that the interproximal tooth surface is the most difficult to clean and cannot be effectively cleansed with a toothbrush only. Significant differences were seen in gender regarding the cleaning of teeth (P ≤ 0.001), the challenging surface of the tooth to clean (P ≤ 0.01), reasons for bad breath (P ≤ 0.003), knowledge of gum disease (P ≤ 0.000) and information regarding interdental cleaning (P ≤ 0.000). Practical Implication: Imparting knowledge regarding the maintenance of oral hygiene is crucial due to the connection between the oral cavity and the rest of the body. In a developing country like Pakistan, awareness, and understanding of oral hygiene is not up to the mark even in the medical population. Hence, improvement in oral hygiene can be brought about by creating public awareness regarding interdental aids in addition to brushing alone. Conclusions: Outcomes of the existing research propose that the overall understanding and awareness amongst medical undergraduates related to interdental aids was satisfactory. Established on these conclusions, additional communal-focused oral health promotions are requisite to piloting the degree of the dwelling of medical undergraduates. Keywords: Awareness, Dental, Dentist, Interdental area, Gingivitis, Knowledge, Medical Undergraduates, Oral Health, Periodontitis, Plaque.